Influence of georeference for GIS based saturation excess overland flow modelling - Mohamad Yusoff, Izham (Penerbit UTM, 2008)
The transformation of geographical data (e.g. actual locations and physical characteristics of objects on the Earth surface) into geographic information dealt with complex series of process and procedures. In saturation excess overland flow (SEOF) modelling, streamflow is one of the main physical geographic apprearance within nature of overland flow cycle. Agriculture, mining, industrial, urbanization, recretion and forest harvesting are major potential increases impervious area causing hazardous impact towards rate of stormwater infiltrated into soil. Thus the overland flow in a postdevelopment area becomes greater than the pre-development area. Within GIS, all stream networks, surface structures and its properties must be assigned and preserved with coordinate systems and map projections respectively known as georeferencing.